2018
DOI: 10.1111/idh.12349
|View full text |Cite
|
Sign up to set email alerts
|

Root surface alterations following manual and mechanical scaling: A comparative study

Abstract: All periodontal devices used in this in vitro study produced a certain degree of surface alteration. Hand curettes appear to have a major impact on surface integrity compared with piezoelectric ultrasonic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…This study presented certain limitations, such as the absence of application angles other than 0 • and 45 • and time settings other than 60 s. There was also a lack of lateral force executions. However, it should be kept in mind that the lateral force implementation is not easily replicated or standardized [36]. Nevertheless, within these limits, our findings provided information on certain comparisons, including root-surface alterations after the use of widely preferred conventional dental hygiene instruments.…”
Section: Discussionmentioning
confidence: 92%
“…This study presented certain limitations, such as the absence of application angles other than 0 • and 45 • and time settings other than 60 s. There was also a lack of lateral force executions. However, it should be kept in mind that the lateral force implementation is not easily replicated or standardized [36]. Nevertheless, within these limits, our findings provided information on certain comparisons, including root-surface alterations after the use of widely preferred conventional dental hygiene instruments.…”
Section: Discussionmentioning
confidence: 92%
“…[56] UD-SRP comparisons present and different PPD categories in the same study or experimental group. [57,58] A n in vitro study. [10,59] Uncertain sample size.…”
Section: B) Initial Ppd > 4 MMmentioning
confidence: 99%
“…Although the scaling procedures performed with HI have been considered the standard treatment for periodontal disease, this procedure is difficult to perform, and the degree of the root surface roughness promoted by this treatment indicates that the root surfaces should be polished after the scaling 16,17 , as confirmed by this study. Additional tools for non-surgical periodontal treatment, such as US and RI, have been proposed to facilitate the scaling procedure 8,12 ; however, this study showed that the use of these alternatives does not eliminate the necessity to polish the root surfaces.…”
Section: Discussionmentioning
confidence: 79%
“…The best combination of treatment found in this study was US in addition to polishing with the prophylactic 3% hydroxyapatite paste. The application of US on the root surfaces has been shown to produce a reduced or equal root surface roughness than that produced by HI 8,25 , which may suggest that the polishing procedure can be applied for shorter times than for surfaces treated with the other tools. In addition, the US treatment has also been shown to remove less dentin tissue compared to other instruments 25 , which may also facilitate obtaining a more polished surface and reducing the possibility of dentin hypersensitivity after scaling since the superficial dentin layers present fewer dentinal tubules and a reduction in tubule diameter 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation